UV spectroscopic monitoring of vaporized monoaromatic hydrocarbons from petroleum-contaminated soils - Kim, Woo Jin; Lee, Joo In; Lee, Seockhun; Ahn, Kyu-Hong; Park, Jae-Woo (SPRINGER, 2006)
Fast and simple systems using ultraviolet (UV) absorbance were examined for on-line monitoring of monoaromatic hydrocarbons from petroleum-contaminated soils in this research. Since soil particles hinder the UV light transmittance, the absorbance measurement of vaporized monoaromatic hydrocarbons in soil gas extracted from petroleum-contaminated soils was proposed. In the fixed system that exhibited higher sensitivity than the portable one, the absorbance intensity of benzene, toluene, ethylbenzene, and xylene increased in proportion to the concentration of the contaminants. The portable system, however, was suitable for screening purpose, while it exhibited faster response. There was no interference from water, which helps the applicability of the proposed systems to the actual fields.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; LASER-INDUCED FLUORESCENCE; SOLID SAMPLES; WATER; EXTRACTION; SENSOR; PRODUCTS; REMOVAL; SYSTEM